Costs and economic viability of the production and marketing of pickled canned trout (Oncorhynchus mykiss) - Yépez-A., Sara G. (2023)
Puno is the first rainbow trout producing region in Peru. The objective of the study was to study the feasibility of giving added value to trout. The cost analysis and financial viability of the production of six types of canned pickled trout preserves were considered. The fillets were obtained from trout fed with three commercial foods (Salmofood®, Naltech® and Tomasino®) and the preserves had two presentations (can vs. glass). The production costs were calculated through a documented record of data at market prices. The general theory of production costs was applied and through the cash flow financial tool the profitability indicators were found. The financial net present value (NPVf) was positive for all six presentations. The internal rate of return (IRR), both for canning (34.5, 37.5 and 42.8%) and for glass canning (34.7, 38.2 and 44.3%) was higher than the opportunity cost of capital (COK) and in both cases, the benefit-cost ratio (B/C) was similar and greater than one (1.05, 1.06 and 1.07) for the three commercial foods, respectively. The capital recovery period was between 5 and 6 years for the two types of preserves. In conclusion, the pickled trout canning project is profitable and, therefore, its investment is recommended to contribute to the sustainability of production and improve the income of producers in the region.